The Role of Substance Use and Resiliency Factors on Suicidal Ideation among Middle School Students. (11th December 2019) - Greene, Naomi; Tomedi, Laura; Reno, Jessica; Green, Dan
ABSTRACT: BACKGROUND: Suicidal ideation, an important risk factor for suicide, is strongly associated with substance use. Factors such as family cohesion, connection with friends, and social support can be protective against suicidal behaviors. The purpose of this study was to explore the association between suicidal ideation, substance use, and resiliency factors among middle school students. METHODS: The 2013 New Mexico Youth Risk and Resiliency Survey provided the data for this analysis. Suicidal ideation was defined as affirmative responses to questions about thoughts of killing oneself and/or making a suicide plan. We used logistic regression to explore the association between suicidal ideation, substance use, and resiliency factors. RESULTS: Overall, 23% of students reported suicidal ideation. Among girls, having a caring friend was associated with lower odds of suicidal ideation only among those not using other drugs. Among boys, having a caring friend decreased the odds of suicidal ideation regardless of substance use. CONCLUSIONS: Suicidal ideation is prevalent among middle school children. Substance abuse is associated with suicidal ideation; however, individual and community support can be protective. Interventions aimed at reducing suicidal behaviors among middle school students should account for the impact of substance use and help strengthen social support.